CHALLENGES AND SOLUTIONS OF INTEGRITY IN CLASSROOM BASED ASSESSMENT (CBA): A CASE STUDY IN HULU SELANGOR - Nik Muhammad Hanis; Muhammad Ihsan; Mohd Afifi Bahurudin; Mohd Syaubari Othman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The integrity of Classroom Based Assessment (CBA) in schools’ contexts poses unique challenges due to the diverse social, cultural, and educational backgrounds of students. This article aims to explore the challenges and solutions related to maintaining integrity in CBA within multiracial school. Using a qualitative approach, six teachers, who are also master trainers (Jurulatih Utama) were interviewed, employing purposive sampling to gather in-depth insights. The findings reveal key challenges related to integrity, including issues of transparency, honesty, justice, humility, moral courage, and consistency in assessment practices. In response to these challenges, the study proposes several solutions, such as strengthening value-based education, offering comprehensive training and professional development for educators, and placing greater emphasis on transparency and accountability in assessment. This research concludes that the integrity in Classroom Based Assessment is important, as it will affect the whole system of education and teachers play vital roles in ensuring professional Classroom Based Assessment established in schools.